Diagnostic Value of Gd-EOB-DTPA-MRI for Hepatocellular Adenoma: A Meta-Analysis - Guo, Yongfei (J Cancer, 2017)
Objective: This study aimed to systematically review the gadoxetic acid-enhanced magnetic resonance imaging (Gd-EOB-DTPA-MRI) findings of hepatocellular adenoma (HCA), especially focusing on the diagnostic value of low signal intensity (SI) in the hepatocyte-phase (HBP) for differentiating HCA from focal nodular hyperplasia (FNH). Methods: A thorough literature search was conducted in PubMed, Excerpta Medica Database (EMBASE) and China National Knowledge Infrastructure databases (CNKI) to identify studies evaluating Gd-EOB-DTPA-MRI presentations of HCA. Published studies using pathological examinations as the gold standard were included. The pooled proportions of low SI in the HBP, arterial-phase, portal venous-phase (PVP) in HCA were calculated, as well as pooled proportions of bleeding, fatty degeneration, and central scar. Meta-analysis was used to evaluate the diagnostic value of low SI in the HBP for HCA. Results: The search yielded 90 studies, with 8 assessing a total of 256 HCA cases included in this study, total of 229 lesions showed low signal in the HBP. Pooled proportions of low SI in the arterial-phase, PVP, and HBP were 2% (95% CI: 0.01-0.05), 39% (95% CI: 0.25-0.55), and 89% (95% CI: 0.80-0.94), respectively. Pooled proportions of bleeding, fatty degeneration, and central scar in HCA were 11% (95% CI: 0.03-0.19), 37% (95% CI: 0.27-0.49), and 10% (95% CI: 0.03-0.27), respectively. The meta-analysis revealed the following characteristics of low SI in the HBP for HCA diagnosis: 1) pooled sensitivity, 0.917 (95% CI: 0.86-0.96); 2) pooled specificity, 0.952 (95% CI: 0.91-0.98); 3) pooled positive likelihood ratio, 15.028 (95% CI: 7.10-31.82); 4) pooled negative likelihood ratio, 0.105 (95% CI: 0.07-0.17); 5) area under the ROC, 0.9802 (Q value of 0.9375), The sensitivity analysis showed that no single study was found to influence the overall pooled estimates significantly, which indicated the stability of the meta-analysis results were good. Conclusions: Low SI on the HBP of Gd-EOB-DTPA-MRI was helpful for the diagnosis of HCA and differentiating from FNH, but it was overvalued, especially for some HCA pathological subtypes. Combining low SI in the HBP with routine MRI presentations and the risk factors of liver diseases could substantially improve its diagnosis value for HCA as well as differential diagnosis.